Image Analysis as a Tool for Estimation of Red Peppers’ Color - Ramesh Babu Natarajan; Ranjith Arimboor (Food ScienTech Journal, 2022)
Red pepper is an excellent source of natural red color. The estimation of color is of great importance, as it is being used for grading red peppers to suit various applications in the food industry. A novel method for quick and easy determination of the color of red peppers by analyzing the color images obtained from a flatbed scanner was developed and validated. ImageJ software was used for measuring the RGB values of the images and the RGB values thus obtained were converted into the industrially accepted American Spice Trade Association (ASTA) color values in red peppers by using an empirical formula. The results were compared with color values obtained through ASTA chemical analytical method. The developed image analysis method was used for the analysis of red peppers with color values ranging from 15 to 154 ASTA units. The image analysis method showed good agreement with the chemical method for color values ranging from 40 to 140 ASTA units. The new method is also fast and easy to adopt and is deemed useful in the field, of processing and storage facilities, where access to sophisticated instrumentation for color estimation and color stability studies is limited.